A decade of dissent: explaining the dissent voting behavior of Bank of England MPC members - Harris, Mark; Levine, P.; Spencer, C. (Springer New York LLC, 2011)
We examine the dissent voting record of the Bank of England Monetary PolicyCommittee. Contrary to findings in the FOMC literature (for example Havrilesky andSchweitzer in The Political Economy of American Monetary Policy, pp. 197–210, 1990;Chappell et al. in Q. J. Econ. 108(1):185–218, 1993), the effects of members’ career backgroundsand the political channel of appointment on voting behavior are negligible, reflectingthe distinct institutional constraints and incentives associated with UK monetarypolicy. Our findings also suggest that literature which characterizes voting behavior as beingpredominantly determined by members’ internal or external status is overly simplistic.This view is supported by econometric results appertaining to the introduction of memberspecificfixed-effects, which account for possible unobserved heterogeneity.